The Effect of Student Resilience and Self-Regulated Learning On Academic Achievement - Risa Cahya Maulani Falencya Galizty; Nani Sutarni (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the effect of student resilience and self-regulated learning on student academic achievement in economics subjects. The research method used is an explanatory survey using a questionnaire as a data collection. The population in this study were students of class XI and XII of Social Science senior high school in Cianjur regency for the academic year 2021/2022 and a sample of 237 students was taken using simple random sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that resilience and self-regulated learning had an effect on students' academic achievement in economics subjects